CONTRIBUTION OF LINGUISTICS TO MODERN DEVELOPMENT - Meliqulov Mahmud Jumanazar o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
In this article, you can learn about the contribution of linguistics methodology to the development. Today there are many types of linguistics, and we can give examples of unfamiliar ones. Internal laws of language development, stages of its development, laws of its development, internal and external factors of language development, internal linguistics, phonetic development, lexicological issues of grammatical development are mentioned.